Perioperative management of caesarean section for a pregnant woman with Sjögren's disease and pulmonary embolism: a case report - Liu, Fanghao; Wang, Xiaohui; Yuan, Shu; Xu, Lin; Shan, Kaiyue; Wang, Longfei; Huang, Jianting; Zheng, Qiang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundSjögren's disease (SjD) is a chronic inflammatory autoimmune disease with significant female predominance, characterised by lymphocyte proliferation and progressive damage to exocrine glands. The complexity of the condition of women with SjD and the incidence of complications substantially increase during pregnancy, which undoubtedly has consequences on both maternal health and neonatal outcomes. Pulmonary embolism (PE) is associated with increased perinatal mortality. However, PE has rarely been reported in pregnant women with SjD.Case presentationA 40-year-old pregnant woman was diagnosed as having SjD. During admission, she experienced chest tightness and suffocation and was scheduled for caesarean section under combined spinal-epidural anaesthesia because of sustained low oxygen saturation and foetal distress. Postoperative pulmonary artery computed tomography angiography confirmed that the patient had developed a pulmonary embolism during the perioperative period. After multidisciplinary consultation, the patient underwent inferior vena cava filter implantation, anticoagulation, oxygen therapy, and anti-infection therapy; both the mother and neonate recovered and were discharged.ConclusionEarly identification and comprehensive perioperative monitoring during the prenatal period are vital in patients with SjD complicated by PE.